Russia-China Relations : Alliance in the Making? - Cheang, Chris (2018)
The meeting between Vladimir Putin and Xi Jingping in Vladivostok on 11 September 2018 and the first-ever participation of Chinese units in the Vostok-2018 military exercise have renewed speculation about the emergence of a Russia-China alliance. While ties are certainly strengthening, an alliance between them is still difficult to imagine.